2022
DOI: 10.3390/nu14112283
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Diet and Meal Timing in a Randomized Controlled Feeding Study of Time-Restricted Feeding

Abstract: Adherence is critical in feeding studies to determine the efficacy of dietary interventions. This time-restricted intake of meals (TRIM) investigation was a controlled feeding study that randomized 41 participants to follow 12 weeks of time-restricted feeding (TRF) or a usual feeding pattern (UFP). Adherence was optimized through careful screening and participant orientation, flexibility in beverages and seasonings, and frequent contact between participants and staff. Adherence was measured daily using a self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Note that a full list of the articles supported through this center is included within the reference section. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Figure 2 summarizes the center's key accomplishments.…”
Section: Obesity Sfrns : Goals and Resultsmentioning
confidence: 99%
“…Note that a full list of the articles supported through this center is included within the reference section. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Figure 2 summarizes the center's key accomplishments.…”
Section: Obesity Sfrns : Goals and Resultsmentioning
confidence: 99%
“…Some research suggested that the threshold for the effect of TRE strategies was around 12 weeks when the intervention effect was likely to be the best with the highest dietary adherence, after which the effectiveness might decrease as the adherence rate lowered. 11 , 50 Therefore, the relevance of energy balance, the eating window, and body weight need to be rigorously assessed, and more objective measurements of daily energy intake and compliance are needed. 51 Although the weight loss magnitude was modest, subgroup analysis indeed showed the advantage of eating time-of-day in TRE.…”
Section: Discussionmentioning
confidence: 99%
“…Most were 8 and 12 weeks and lacked follow-up on the long-term effects of TRE strategies. Some studies 11 , 51 suggested that the intervention effect of TRE showed an inverted U-shaped curve that increased initially and then decreased with the intervention duration. However, in this meta-analysis, we were not able to perform a nonlinear meta-regression to test this hypothesis due to the limitations of the intervention duration lengths in the included studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations